Influence of cetiltrimethylammonium bromide in degradation of endosulfan in soil - Muniz, Edvani Curti; Rubio, Danil Agar Rocha (Pesquisa Agropecuaria Brasileira, 1993)
The degradation of the Endosulfan in soil was studied, in presence of cetyltrimethylammonium bromide (CTABr). After application of the pesticide in the soil, samples were collected periodically and analised by Gas Chromatography. It was verified that 60 days after application, its concentration in presence of the CTABr is half of that encountered in the absence of the surfactant, showing that the CTABr increases the rate of degradation of Endosulfan in soils. The half-life time of pesticide in soil with surfactant is 56 days and in soil without surfactant, 138 days. It was also verified that the concentration of CTABr have not great influence in the velocity of degradation of Endosulfan, i.e., the concentration of pesticide is nearly the same in the range of CTABr studied.